Vaccine Dosing Considerations in Product Labels and ACIP Recommendations: A Review - Kunal Saxena; Kate Mevis; Sofia Toso; Elif Alyanak; Natasha Hansen; Aliana Potter; Molly Flannery; Mona Saraiya (Vaccines)
In the United States, the Food and Drug Administration (FDA) is the regulatory authority with the responsibility to evaluate scientific data included in each vaccine’s prescribing information (e.g., safety, indication(s) for use, and dosing schedule) based on several factors, including safety, quality, potency, and effectiveness in preventing disease to assess benefit/risk prior to approval. After approval, the FDA continues to work with sponsors to ensure safety and effectiveness data in the prescribing information remain current. In conjunction with FDA approval or authorization, the Advisory Committee on Immunization Practices (ACIP) recommends immunization dosing schedules and target populations for use. ACIP recommendations that are adopted by the Centers for Disease Control and Prevention (CDC) Director inform national immunization schedules, which influence immunization access, coverage, and provider behavior. This targeted review aims to explore historical instances when vaccine dosing regimens approved by the FDA differ from those recommended by the ACIP, focusing on the frequency and factors behind these differences to inform future ACIP recommendations. Out of n = 78 vaccines assessed, the analysis identified n = 5 vaccines with deviations and only one that reduced dosing. Deviations from the FDA label were determined to be a rare occurrence and are most frequently observed to be additive, not reductive.